PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). C.N. Barnard and the first clinical heart transplantation (December 3, 1967). V.P. Demikhov and C.N. Barnard: touchpoints - S. P. Glyantsev; B. M. Gorelik; A. Werner (Трансплантология (Москва))
Having studied the available printed, visual, and verbal sources from Russia, South Africa, the USA, and Germany, we have identified and reviewed in the article the facts of face-to-face and correspondence communication between V.P. Demikhov, the "father" of experimental heart transplantation (Moscow, USSR), and C.N. Barnard, a pioneer of clinical heart transplantation (Cape Town, South Africa). We have shown that C.N. Barnard mastered the heart surgery techniques, including those under conditions of artificial circulation, in the USA in 1956-1958, and later improved them in his homeland both in clinic (heart surgery for cardiac defects), and in the experiment (heart transplantation). The main events preceding the first world human heart transplant performed by C.N. Barnard on December 3, 1967, were his trip to the United States in August 1967 to study immunosuppression techniques, and the kidney transplantation he had performed in Cape Town in September, 1967. Prior to that time, C.N. Barnard had visited the USSR only once, in May 1960, as a delegate to the XXVII All-Union Congress of Surgeons. In the Soviet Union, he visited a number of clinics dealing with heart surgery and tissue and organ transplantation, including the N.V. Sklifosovsky Institute for Emergency Medicine, where he met V.P. Demikhov, but C.N. Barnard could neither talk to him personally, nor watch his operations. In December 1967, V.P. Demikhov spoke with C.N. Barnard on the phone, but the conversation was highly professional. This paper has shown different approaches of V.P. Demikhov and C.N. Barnard to the transplantation problem: the Soviet surgeon paid more attention to the transplantation technique, meanwhile, the South African surgeon considered the solution of immunological problems to be the basis of success. Nevertheless, C.N. Barnard knew about V.P. Demikhov's scientific achievements and used some of them in his surgical practice. The authors have substantiated the interaction between V.P. Demikhov and C.N. Barnard as between an ideological mentor and a student (in a broad sense) rather than as a teacher and a student (in a narrow sense). Therefore, in a broad, philosophical sense, the Soviet surgeon can be considered one of the inspirers of the world's first heart transplantation, which, in turn, proved that his ascetic work was not in vain.